The Influence of Experiential Marketing, Emotional Branding, Brand Trust Towards Brand Loyalty - Dewanti, Retno; Chu, Tjia Fie; Wibisono, Steven (Binus Business Review, 2011)
The restaurant business in jakarta showed rapidly increased. Marketing today as the compete of brand strategy and experiental marketing on the competitive situation. The Jun Jan Kitchen is a new restaurant specialized on Chinnese Food, urgent to know the brand loyalty. The Aim research is to measured the influence of Experiental marketing, emotional branding and brand trust towards brand loyalty. Research method used descriptif, data collecting technique with questioner and observation. Statistic tools using path analysis to looking for contribution level on each variabel towards other. Population this research is customer Jun Jan Kitchen. Sampling technique using accidental sampling. Amount of sample is 100 customers. Result of this research is experiental marketing giving the significant influence towards brand trust whereas Emotional branding giving the significant influence towards brand loyalty.Â